ANALISIS PERILAKU KONSUMSI PADA MARKETPLACE (SHOPEE & TOKOPEDIA) MENGGUNAKAN MODEL UTAUT - Ni Putu Suci Meinarni; Ni Putu Ratih Pradnya Dewi; Wayan Gede Suka Parwita (Prahasta Publisher, 2022)
Using a marketplace platform for trade transactions in the digital era is currently in great demand than conventional shopping. However, marketplace users cannot just give away their personal data just like that. Customer data security is the most important thing that must be considered in order to avoid computer network crimes or commonly known as cybercrime. This article aims to find out what influences the security of customer data in the marketplace on consumer shopping behavior by implementing the UTAUT (Unified Theory of Acceptance & Use of Technology) research model. The research method in this article uses descriptive quantitative methods by taking population samples of active marketplace users in Denpasar City and using samples from several respondents. In this article it can be concluded that interest in using the marketplace has a partial influence on user behavior and the facilitating condition variables moderated by experience have a simultaneous effect on user behavior. These factors are proven to both have important aspects in influencing the security of customer data on the marketplace.